The Role of Financial Literacy in the Financial Management of Young Families (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Financial Financial management plays a crucial role in enabling families to plan, allocate, and control their finances effectively, thereby supporting long-term financial well-being. This study aims to examine and analyze the direct and indirect effects of lifestyle and income on financial management, with financial literacy serving as a mediating variable, among married women aged 19 to 24 years in Klaten Regency. Employing a quantitative research design, data were collected through a structured questionnaire distributed via Google Forms. The study population comprised all residents of Klaten Regency, totaling 1,302,648 individuals. Using the Slovin formula and specific criteria—married women within the specified age range—a sample of 100 respondents was obtained. Data analysis was conducted using Smart PLS 4 software to evaluate the structural relationships between variables. The findings indicate that lifestyle has a direct and significant effect on financial management but does not significantly influence financial literacy. Conversely, income does not have a significant direct effect on financial management, yet it significantly influences financial literacy. Furthermore, financial literacy has a direct and significant effect on financial management. Mediation analysis reveals that financial literacy successfully mediates the relationship between income and financial management, but it does not mediate the relationship between lifestyle and financial management. These results highlight the importance of improving financial literacy as a pathway for enhancing financial management, particularly for individuals with varying income levels. The study contributes to the literature by providing empirical evidence on the role of financial literacy as a mediator in the context of young married women, offering valuable insights for policymakers and financial education practitioners aiming to foster financial well-being in young families.